Investigating the Variable of Spiritual Inclination’s Moderating Effect between Teachers’ Perceived Stress Levels and Common Anxieties - Okan, Nesrullah (BİLGE AKADEMİK YAYINCILIK EĞİTİM BİLİŞİM VE DANIŞMANLIK HİZMETLERİ, 2021)
This research aims to examine in the context of the structural equation model the moderating effect of spiritual orientation on the relationship between the situation of common anxiety and the levels of perceived stress in individuals who teach at different types of schools. Similarly, addressing teachers’ perceived stress levels, common anxieties, and spiritual orientations in the context of various demographic variables is an aim of the present study. The research universe included teachers working at various school levels in the 2018-2019 school year in the Anatolian side of the Province of Istanbul. The research sample consisted of 268 teachers from different school levels. Data were obtained using scales for perceived stress, common anxiety, and spiritual orientation and a form on demographic information. In line with the aims of this research, Pearson product-moment correlation analysis and path analysis were used. As a result of the analysis, it was concluded that the variables of stress and anxiety were in a negative and significant relationship with the variable of spiritual orientation (r1=-.305; r2=-.227; p<.001). As a result of the path analysis, spiritual orientation was seen to have a moderating effect on the relationship between perceived stress and common anxiety. The research has been discussed and finalized in light of the literature. Click or tap here to enter text.
Keywords: Other Fields of Education; Alan Eğitimleri